The development of Mathematics Homework Engagement (MHE) instrument for secondary school students, Malaysia - Rajoo, Murugan; Veloo, Arsaythamby (Canadian Center of Science and Education, 2015)
The purpose of this study is to develop the instrument of Mathematics Homework Engagement (MHE) for secondary school students in Malaysia. This study also identifies the relationship between the factors of Mathematics Homework Engagement, namely students, teachers, parents andschool management towards mathematics achievement.The MHE has been used to measure the engagement of students, teachers, parents and school administrators in mathematics homework. This instrument was developed from student’s focus group interviews and the literature review.The results of the analysis was found that these four factors of MHE item instrument ranged from 54.52% to 69.38% of variance related with homework engagement.Croanbach Alpha indicated that the reliability of each factor is reasonable in context of internal consistency which is more than 0.70. Based on the results of validity and reliability, the instrument remained with 15 items, and states that it is sufficient to measure MHE for secondary school students in Malaysia. Pearson correlation coefficient revealed that, there are positive correlations between the factors towards mathematics achievement except for parent’s engagement. In conclusion, this instrument can be used by teachers, counselors, school administration and the Ministry of Education to assess students’ understanding of MHE. With such understanding, teachers can arrange better mathematics homework for their students.